Exploring resilience: The impact of operational efficiency and financial health in South African non-life insurance companies - Omonike Ope Ige-Gbadeyan; Matthys Johannes Swanepoel (Insurance Markets and Companies)
The South African non-life insurance sector faces persistent challenges, including low investment returns, the need for digital transformation, and underperformance in meeting strategic goals. These issues threaten operational efficiency and financial health, critical factors for resilience in a competitive market. This study investigates the relationship between operational efficiency, financial health, and resilience in 32 South African non-life insurance companies. A descriptive research design was employed, analyzing panel data from 2008 to 2019, a period chosen due to the financial crisis of 2008, which significantly impacted the insurance industry. Data were sourced from S&P Capital IQ and Refinitiv Eikon, known for providing reliable financial information. Regression analysis was used to examine how liquidity, leverage, and company size influence financial health, with company size analyzed as a moderating factor.The results showed that liquidity and leverage positively impact financial health, with larger companies benefiting more from operational efficiency and profitability improvements. However, the effect of liquidity decreases as company size increases. The model demonstrated strong explanatory power (R² = 0.8662) and was statistically significant (Wald Chi² = 611.92, p < 0.01). These findings offer actionable insights for industry stakeholders and policymakers, emphasizing the importance of tailored strategies to enhance resilience and sustainable growth across companies of varying sizes. Addressing operational inefficiencies and financial health can strengthen the industry’s capacity to navigate future challenges.